The risk of adverse clinical outcomes following treatment of Plasmodium vivax malaria with and without primaquine in Papua, Indonesia. - Kamala Thriemer; Jeanne-Rini Poespoprodjo; Enny Kenangalem; Nicholas M Douglas; Paulus Sugiarto; Nicholas M Anstey; Julie Anne Simpson; Ric N Price (Public Library of Science (PLoS), 2020)
The widespread use of primaquine (PQ) radical cure for P. vivax, is constrained by concerns over its safety. We used routinely collected patient data to compare the overall morbidity and mortality in patients treated with and without PQ without prior testing of Glucose-6-Phosphate-Dehydrogenase (G6PD) deficiency in Papua, Indonesia, where there is a low prevalence of G6PD deficiency. Records were collated from patients older than 1 year, with P. vivax infection, who were treated with an artemisinin combination therapy (ACT). The risks of re-presentation, hospitalization, major fall in haemoglobin and death within 30 days were quantified and compared between patients treated with and without PQ using a Cox regression model. In total 26,216 patients with P. vivax malaria presented to the hospital with malaria during the study period. Overall 27.56% (95% Confidence Interval (95%CI): 26.96-28.16) of 21,344 patients treated with PQ re-presented with any illness within 30 days and 1.69% (1.51-1.88) required admission to hospital. The corresponding risks were higher in the 4,872 patients not treated with PQ; Adjusted Hazard Ratio (AHR) = 0.84 (0.79-0.91; p<0.001) and 0.54 (0.41-0.70; p<0.001) respectively. By day 30, 14.15% (12.45-16.05) of patients who had received PQ had a fall in haemoglobin (Hb) below 7g/dl compared to 20.43% (16.67-24.89) of patients treated without PQ; AHR = 0.66 (0.45-0.97; p = 0.033). A total of 75 (0.3%) patients died within 30 days of treatment with a mortality risk of 0.27% (0.21-0.35) in patients treated with PQ, compared to 0.38% (0.24-0.60) without PQ; AHR = 0.79 (0.43-1.45; p = 0.448). In Papua, Indonesia routine administration of PQ radical cure without prior G6PD testing, was associated with lower risk of all cause hospitalization and other serious adverse clinical outcomes. In areas where G6PD testing is not available or cannot be delivered reliably, the risks of drug induced haemolysis should be balanced against the potential benefits of reducing recurrent P. vivax malaria and its associated morbidity and mortality.